RAGAM FENOTIP EKSTERNAL TUBUH SAPI LOKAL - Laya, Nibras; Gubali, Syukri; Dako, Safriyanto (Gorontalo Journal of Equatorial Animals, 2025)
The purpose of this study was to identify the variety of external body phenotypes of local cattle raised by the livestock community. This study was conducted in Sumalata District, North Gorontalo Regency, Gorontalo Province. For ± 3 months, from November 2023 to January 2024. A total of 137 female local cattle aged 4-5 years have been recorded for external body characteristics. Descriptive analysis describes the data obtained from the results of observation and documentation. The data obtained in the field are then made into a contingency table. Dominant color, horn shape, leg color and face shape. The body color of local cattle found is dominant white, dominant brick red, dominant black brown, dominant cream, dominant gray, dominant black and dominant brown. The leg colors found in local cattle are Brick Red, White, Black White, White Cream, Brown, Brick Red, Black, Black Brown, and Gray. The leg color of this local cattle almost resembles the leg color of Balinese cattle. The horn shape includes curved forward, curved inward, upright upward, upright sideways, no horns, and short. Meanwhile, the face shape includes flat and convex Keywords: Leg shape, Body color and Local cattle